Diasporic Diffusion: How Cape Verdean Communities Influence Environmental and Educational Policies in their Homeland - Jörgens, H.; Neves, J.M. (International Workshop: “Diasporas and Homeland Governance – Decentering the State as an Analytical Category”, 2017)
Diasporas are increasingly recognized as potentially influential actors in the governance of their countries of origin. So far, much of the literature has focused on their influence on foreign policymaking, both in their homelands and their hostlands (Shain 2007), and on policies that directly affect migrants’s “own legal, economic and political status in their homeland” (Østergaard-Nielsen 2003: 762). In contrast, we know little about whether, how and to what extent diaspora communities abroad have a hand in shaping those domestic policies that do not directly affect their rights as migrants or that don’t relate directly to the foreign relations between their home- and hostlands. To address this research gap, our paper analyses the influence of diaspora communities on the environmental and educational policies of Cape Verde. With a long history of migration and a diaspora that is estimated to be twice the size of its resident population, Cape Verde constitutes a most likely case of diasporic policymaking (Resende-Santos 2016). Over the past 30 years, the country has adopted ambitious political programs in the fields of education and environmental protection that have enabled it, amongst others, to meet the respective Millennium Development Goals (Neves 2010, 2015). In the surrounding policy debates, diaspora communities have been active participants. The first part of the paper presents an analytic framework for understanding processes of “diasporic diffusion” based on concepts of “social” (Levitt 1998) and “political” (Ahmadov and Sasse 2015) remittances. We argue that migrant communities have become important agents of policy diffusion, acting through two distinct pathways. First, they directly feed policy ideas into the Cape Verdean policymaking process. Second, members of the diaspora act as brokers between international policy discourses and domestic politics by lending local credibility and legitimacy to the abstract policy recommendations of international organizations. In the second part of the paper we substantiate our theoretical claims with empirical evidence from the Cape Verdean case study.